2019
DOI: 10.1111/1753-6405.12871
|View full text |Cite
|
Sign up to set email alerts
|

Dual use of electronic cigarettes and tobacco in New Zealand from a nationally representative sample

Abstract: Objective: There is strong interest in the use of electronic cigarettes (e‐cigarettes) globally. Not much is known about the dual use of e‐cigarettes and combustible tobacco cigarettes, or if there are demographic differences among dual users and e‐cigarette only users. This paper reports on the demographics of dual users and e‐cigarette only users in New Zealand in a nationally representative sample. Methods: The Health and Lifestyles Survey (HLS) is a biennial face‐to‐face in‐house survey of New Zealand adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
7
2
Order By: Relevance
“…The estimate of the prevalence of current e-cigarette use from the Behavioral Risk Factor Surveillance System in 2016 was 4.5% [ 31 ]. The overall percentage of dual users in our study was 1.3%, which was slightly lower than that in previous studies from the United States (1.8% to 2.0%) [ 20 , 31 ] and New Zealand (2.7%) [ 12 ]. Importantly, among current e-cigarette users, 84.6% used e-cigarette and c-cigarette concurrently in the present study, and the rate of concurrent use was comparable with the rates reported in other countries: 74% in Germany [ 13 ], 83% in France [ 15 ], 65% in New Zealand [ 12 ], and 76% in Japan [ 14 ].…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The estimate of the prevalence of current e-cigarette use from the Behavioral Risk Factor Surveillance System in 2016 was 4.5% [ 31 ]. The overall percentage of dual users in our study was 1.3%, which was slightly lower than that in previous studies from the United States (1.8% to 2.0%) [ 20 , 31 ] and New Zealand (2.7%) [ 12 ]. Importantly, among current e-cigarette users, 84.6% used e-cigarette and c-cigarette concurrently in the present study, and the rate of concurrent use was comparable with the rates reported in other countries: 74% in Germany [ 13 ], 83% in France [ 15 ], 65% in New Zealand [ 12 ], and 76% in Japan [ 14 ].…”
Section: Discussioncontrasting
confidence: 85%
“…The overall percentage of dual users in our study was 1.3%, which was slightly lower than that in previous studies from the United States (1.8% to 2.0%) [ 20 , 31 ] and New Zealand (2.7%) [ 12 ]. Importantly, among current e-cigarette users, 84.6% used e-cigarette and c-cigarette concurrently in the present study, and the rate of concurrent use was comparable with the rates reported in other countries: 74% in Germany [ 13 ], 83% in France [ 15 ], 65% in New Zealand [ 12 ], and 76% in Japan [ 14 ]. Considering that most e-cigarette users also use c-cigarette, it is challenging to determine the independent effect of e-cigarette on the risk of COPD.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…In 2016, 58.8% of vapers were dual users in France and 63.9% in New Zealand , a prevalence similar to that observed in the United States in 2015 (59%) . According to recent data, dual use comprises 44% of vapers in the United Kingdom .…”
Section: Introductionsupporting
confidence: 57%
“…[40][41][42][43] At the same time, use of ENDS may potentially support continuing smoking and dual use of combustible tobacco cigarettes and e-cigarettes is one of the most common patterns of observed use. [44][45][46] High cost, limitations on places where smoking is allowed, bans on advertising, clear health warnings and reduced social acceptability are all important elements in comprehensive tobacco control. 47 Smokers may potentially be able to mitigate some of these impacts through dual use with ENDS, thereby prolonging smoking, as ENDS are generally cheaper than smoking, are often able to be used in settings where combustible cigarettes are prohibited, their health impacts are less clear and they are often more socially acceptable.…”
Section: Discussionmentioning
confidence: 99%